Advances in Biosensors and Diagnostic Technologies Using Nanostructures and Nanomaterials. (28th July 2021) - Welch, E. Celeste; Powell, Jessica M.; Clevinger, Tobias B.; Fairman, Alexis E.; Shukla, Anita
Abstract: Nanoscale materials have unique properties that make them especially useful for biomedical diagnostic applications. Recent developments in nanoengineering have resulted in increasing use of nanostructures in biosensors. Various types of 0D, 1D, 2D, and 3D nanostructures have been used to improve biosensor sensitivity, selectivity, limit of detection, and time to result, among other metrics. These nanostructures have been integrated into electrochemical, optical, and other biosensors for this purpose. Here, the most recent advances in the use of nanostructured materials in biosensors are described. This includes a discussion of nanoparticles, nanorods, nanofibers, nanopillars, nanowires, nanosheets, indented nanopatterns (nanoholes and nanoslits), nanogaps, nanochannels, nanopores, nanofunctionalized surfaces, and complex hierarchical structures and their unique advantages and applications in biosensors. Clinical applications of these nanobiosensors are also highlighted along with a discussion of the future directions for these materials in diagnostics. Abstract : Biosensors have been instrumental in advancing human health. These devices are used to monitor various biological analytes, helping to detect disease and monitor normal physiologic function. Nanostructured materials have been increasingly integrated into these devices due to their numerous unique properties that can enhance the functionality of biosensors, increasing target specificity and selectivity and lowering limits of detection.